2007
DOI: 10.1152/ajpheart.00741.2006
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive heme oxygenase-1 gene delivery reveals reduced mortality and preservation of left ventricular function 1 yr after acute myocardial infarction

Abstract: -We reported previously that predelivery of heme oxygenase-1 (HO-1) gene to the heart by adenoassociated virus-2 (AAV-2) markedly reduces ischemia and reperfusion (I/R)-induced myocardial injury. However, the effect of preemptive HO-1 gene delivery on long-term survival and prevention of postinfarction heart failure has not been determined. We assessed the effect of HO-1 gene delivery on long-term survival, myocardial function, and left ventricular (LV) remodeling 1 yr after myocardial infarction (MI) using ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 61 publications
1
46
0
Order By: Relevance
“…5 Nevertheless, HO-1 has been used for gene therapy in several experimental animal models of CVD. 10,11,27,28 In the study by Pachori et al 10 Oxidative stress-inducible vectors H Hurttila et al significant induction of endogenous HO-1 was observed, yet HRE-regulated HO-1 overexpression provided an additional benefit. In our study, both in controls as well as 2 Â GCLM-HO-1-transduced HUVECs, 15d-PGJ 2 significantly attenuated TNF-a-induced NF-kB activation and VCAM-1 expression, but the effect was greater in HO-1-transduced cells (Figure 6).…”
Section: Oxidative Stress-inducible Vectorsmentioning
confidence: 98%
“…5 Nevertheless, HO-1 has been used for gene therapy in several experimental animal models of CVD. 10,11,27,28 In the study by Pachori et al 10 Oxidative stress-inducible vectors H Hurttila et al significant induction of endogenous HO-1 was observed, yet HRE-regulated HO-1 overexpression provided an additional benefit. In our study, both in controls as well as 2 Â GCLM-HO-1-transduced HUVECs, 15d-PGJ 2 significantly attenuated TNF-a-induced NF-kB activation and VCAM-1 expression, but the effect was greater in HO-1-transduced cells (Figure 6).…”
Section: Oxidative Stress-inducible Vectorsmentioning
confidence: 98%
“…Preclinical studies for ischemic heart disease employing antioxidants although still at an early stage have shown some promise (Sugamura and Keaney, 2011;Bolli et al, 2004;Cannon, 2005). For example heme oxygenase -1 (HO-1) based gene therapy has been proposed as a therapeutic strategy for ischemic heart disease because the enzyme has a clear antioxidant capacity (Liu et al, 2007). In addition, the products of heme metabolism, carbon monoxide and bilirubin have been reported to possess cytoprotective properties (Poss and Tonegawa, 1997;Stocker et al, 1987).…”
Section: Antioxidant Therapies and Oxidative Stress In Heart Diseasementioning
confidence: 99%
“…Cardiac function is compromised in patients that survive an initial ischemic event and this progressive myocardial impairment leads to heart failure (Liu et al, 2007;Sugamura and Keaney, 2011;Jessup and Brozena, 2003). High levels of reactive oxygen species (ROS) contribute to the process of disease progression in both myocardial ischemia and in models of heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Biliverdin and its endproduct, bilirubin, are both potent antioxidants with demonstrated cell-protective effects in ischemia-reperfusion injury. [15][16][17][18] Importantly, besides these key roles in cell survival, HO-1 has additional, complementary effects that are pro-angiogenic, [19][20][21] antiinflammatory, 8,9,18,[22][23][24] and anti-fibrotic, 12,23,[25][26][27] all of which would be highly desirable in implanted engineered tissues.…”
Section: Introductionmentioning
confidence: 99%